INVESTIGATION OF QUANTITATIVE ELEMENTAL COMPOSITION OF CHICORIUM INTYBUS L. PLANT (Scientific journal of the Fergana State University, 2023)
Inductively coupled plasma mass-spectrometry (ICP MS) was used to quantify 44 macro and microelements in the flowers of Tansy. The largest macronutrients in quantitative terms: Ca-3964, K-3645, Na-2328, P-1555, S-384, Mg-367, Si-273mg/kg. The amount of iron at the level of macronutrients Fe-360, The amounts of important trace elements are as follows: Al-60, Sr-24, Cu-10, Ba-7,937, Zn-6, Mn-4,7 mg/kg. A comparative analysis was performed with samples from two different growth sites. Although the samples taken from Kuvasoy district of Fergana region are slightly different compared to the samples taken from Beshbola district of Fergana region, the general trend can be said to be close.